Homogeneous photosensitization of complex TiO2 nanostructures for efficient solar energy conversion - Luo, Jingshan (2013)
TiO2 nanostructures-based photoelectrochemical (PEC) cells are under worldwide attentions as the method to generate clean energy. For these devices, narrow-bandgap semiconductor photosensitizers such as CdS and CdSe are commonly used to couple with TiO2 in order to harvest the visible sunlight and to enhance the conversion efficiency. Conventional methods for depositing the photosensitizers on TiO2 such as dip coating, electrochemical deposition and chemical-vapor-deposition suffer from poor control in thickness and uniformity, and correspond to low photocurrent levels. Here we demonstrate a new method based on atomic layer deposition and ion exchange reaction (ALDIER) to achieve a highly controllable and homogeneous coating of sensitizer particles on arbitrary TiO2 substrates. PEC tests made to CdSe-sensitized TiO2 inverse opal photoanodes result in a drastically improved photocurrent level, up to ~15.7 mA/cm2 at zero bias (vs Ag/AgCl), more than double that by conventional techniques such as successive ionic layer adsorption and reaction.